Experimental Investigation of Bladeless Power Generator from Wind-induced Vibration - La Ode Ahmad Barata; Kiwata Takahiro; Toshiyuki Ueno; Samhuddin Samhuddin; La Hasanudin (International Journal of Renewable Energy Development, 2022)
The power harvester unit from flow-induced vibration (FIV) was designed to harness energy from low flow velocity based on the magnetostrictive effect on the galfenol (Fe – Ga alloy) strip induced by the oscillating bluff body. This study aimed to investigate the cross-section variation’s effect on the FIV characteristics and the magnetostrictive material’s performance for the bladeless power generator. The generator model’s vibration characteristics and performance tests were conducted in the wind tunnel test using the wind-receiving unit (WRU) variation. The results showed that the resonance reduced-velocity (Vr) were around 3.7 and 4.0 for rectangular and circular cylinders, respectively. Furthermore, the effect of rectangular depth variation on the power generation output is linear to the test models’ displacement rate and vibration frequency. The harvester’s maximum power generation was 5.25 mW, achieved using the rectangular prism with depth D = 0.4H. The power coefficient was also evaluated for different wind-receiving models. The harvester model lit up 54 LED lamps in the wind tunnel test. The voltage output is sufficient to provide electric power resources for an IoT system, sensor, and wearable or wireless devices. The harvester model successfully generated a voltage signal under the initial field test with an ambient wind velocity of 0.9 – 2.71 m/s. Therefore, this study recommends the development of bladeless power generators in the future.